PENDEKATAN KONTEKSTUAL (CTL) DAN IMPLIKASINYA DALAM PEMBELAJARAN MATEMATIKA - ISRA NURMAI YENTI (Ta'dib, 2009)
Contextual teaching and learning (CTL) is one of approach that able to increase learning teaching quality. This approach can be applied to all academic material not only social  but also science. The  characteristic of this approach is the student directly gets the experience in learning process, so that learning is meaningfull. For mathematic, students is hoped to get knowledge by construct it, not to transfer it from another person.Kata Kunci: pendekatan kontekstual, implikasi, pembelajaran matematika